2017
DOI: 10.1111/dom.12940
|View full text |Cite
|
Sign up to set email alerts
|

Salsalate improves glycaemia in overweight persons with diabetes risk factors of stable statin‐treated cardiovascular disease: A 30‐month randomized placebo‐controlled trial

Abstract: Objective To assess long‐term efficacy and safety of salsalate to improve glycemia in persons with diabetes risk, who are overweight with statin‐treated, stable coronary heart disease. Methods Glycemic status was assessed in 192 persons without diabetes at baseline in a pre‐specified secondary analysis from Targeting INflammation Using SALsalate in CardioVascular Disease (TINSAL‐CVD), a multi‐center, double‐masked, randomized (1:1), placebo‐controlled, parallel clinical trial. Results Participants were mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
0
9
1
2
Order By: Relevance
“…Similarly, the induction of autophagy may reduce atherosclerosis and improve plaque stability, further supporting the possible beneficial role of activating macrophage AMPK 255 . However, recent clinical trials with salsalate in combination with statin therapy for 30 weeks reported no reductions in atherosclerosis compared with statin therapy alone, suggesting that there may be limited therapeutic opportunities for exploiting this pathway for the treatment of CVD 256 ; however, there were improvements in glycaemia, supporting the potential role for this therapy in people at high risk of developing type 2 diabetes 257 . Further studies in mice with AMPK-activating and AMPK-inactivating mutations are now needed to determine whether targeting this pathway may be effective in reducing atherosclerosis and blood glucose.…”
Section: ) (Table 1)mentioning
confidence: 99%
“…Similarly, the induction of autophagy may reduce atherosclerosis and improve plaque stability, further supporting the possible beneficial role of activating macrophage AMPK 255 . However, recent clinical trials with salsalate in combination with statin therapy for 30 weeks reported no reductions in atherosclerosis compared with statin therapy alone, suggesting that there may be limited therapeutic opportunities for exploiting this pathway for the treatment of CVD 256 ; however, there were improvements in glycaemia, supporting the potential role for this therapy in people at high risk of developing type 2 diabetes 257 . Further studies in mice with AMPK-activating and AMPK-inactivating mutations are now needed to determine whether targeting this pathway may be effective in reducing atherosclerosis and blood glucose.…”
Section: ) (Table 1)mentioning
confidence: 99%
“…Treatment of PCOS patients with salicylates resulted in lower levels of ROS, NF-κB and TNF-α and stabilised androgens [ 165 ]. Nevertheless, salicylates should be administered with care due to the number of adverse effects, such as altered cardiorenal functions and hypoglycemia [ 166 ].…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%
“…), resulting in the loss of β cell secretory function, β cell dedifferentiation, and eventual apoptosis-mediated cell death ( Donath et al, 2003 ). Similarly, the chronic low-grade systemic inflammation observed in T2D activates similar signaling cascades, including NF-κB, signaling, which has been a pharmacological target in clinical studies using salsalate ( Fleischman et al, 2008 ; Goldfine et al, 2008 ; Salastekar et al, 2017 ) and the IL-1 receptor antagonist anakinra ( Larsen et al, 2007 ). In this study, we provide evidence suggesting that pro-inflammatory cytokines also promote β cell functional failure through stimulation of β cell small EV secretion, which likely acts in a paracrine/autocrine manner to induce β cell dysfunction and enhance immune cell recruitment.…”
Section: Discussionmentioning
confidence: 99%